The Effect of Entrepreneurship Orientation on Innovation, Competitive Advantage and Company Performance on Shipping Companies - Zarkasi, Mohamad Imam; Arifin, Zainul; Rahimah, Anni (School of Business, IPB University (SB-IPB), 2023)
Covid-19 has spread to various countries and greatly impacted various companies, including shipping companies. Due to the pandemic, the Indonesian shipping sector is experiencing enormous uncertainty and pressure. This research investigates the effect of entrepreneurship orientation on innovation, competitive advantage, and company performance. Quantitative methods were used to analyze 127 shipping companies' leader insights. The sampling method used is probability sampling with a proportionate random sampling technique. The data was analyzed by Structural Equation Modeling (SEM) analysis with a Partial Least Square approach using the Smart-PLS 3.0 program. Entrepreneurship orientation was found to have a significant positive effect on innovation and competitive advantage. Further, innovation has a significant positive effect on competitive advantage and company performance. Ultimately, competitive advantage has a significant positive effect on company performance, and entrepreneurship orientation has an insignificant positive effect on company performance. This research concludes that better management of entrepreneurship orientation will enhance innovation and competitive advantage while maximizing innovation will enhance competitive advantage and company performance. However, the seafaring activities during the pandemic are not intended to take many risks to the company's performance. Keywords: covid-19, entrepreneurship orientation, innovation, competitive advantage and company performance